Effect of omeprazole, claritomycine and amoxiciline therapy on duodenal ulcer and Helicobacter pylori eradication - Vedat GÖRAL; Mehmet TAŞ; Kadri GÜL; Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2019)
-